Design a Touchless Automatic Light Control System as a Facility and Breaker Effort Covid-19 Chain in 2nd Floor, Building I of University Pembangunan Panca Budi - Iqbal Iqbal; Hamdani Hamdani; Siti Anisah (Sean Institute, 2022)
Lighting in a room is usually operated manually by humans. With the advancement of technology today, the operation of human work is getting less and more easy. The Touchless Automatic Switch can turn the lights on and off without touching/pressing the switch, so it will be able to facilitate the operation of the work. In addition, with the design of this switch installation, it is expected to reduce and minimize contact between people indirectly so that health protocols maintain distance and do not touch each other during the Covid-19 pandemic can be applied better. The Touchless Automatic Switch is a device designed with a working system with a program identifying the move through the sensor emitted from the device. Therefore, it is necessary to move/wave the hand directed/close to the sensor surface on the device so that the lamp can turn on and off automatically. Switch installation design is used to operate the load of lighting lights of a room automatically